High Field Linear Magnetoresistance Sensors with Perpendicular Anisotropy L10-FePt Reference Layer - X. Liu; Z. L. Song; R. Wang; Z. Y. Quan (Advances in Condensed Matter Physics)
High field linear magnetoresistance is an important feature for magnetic sensors applied in magnetic levitating train and high field positioning measurements. Here, we investigate linear magnetoresistance in Pt/FePt/ZnO/Fe/Pt multilayer magnetic sensor, where FePt and Fe ferromagnetic layers exhibit out-of-plane and in-plane magnetic anisotropy, respectively. Perpendicular anisotropy L10-FePt reference layer with large coercivity and high squareness ratio was obtained by in situ substrate heating. Linear magnetoresistance is observed in this sensor in a large range between +5 kOe and −5 kOe with the current parallel to the film plane. This L10-FePt based sensor is significant for the expansion of linear range and the simplification of preparation for future high field magnetic sensors.